Pengabdian Berbasis Lomba Keagamaan pada Momen Peringatan Maulid Nabi Muhammad SAW - Hidayah, Nur Fitri; Zarhasih, Ustwatun Umi; Mubarok, Ramdanil (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2025)
This dedication is carried out in the form of a religious competition in order to commemorate the Maulid of Prophet Muhammad SAW. The purpose is to increase the love of the Prophet, to promote Islamic pride, to educate the young generation, to motivate children to study religion, and to spread the good message to the wider community. The method used in this dedication is the participatory action research method (PAR). The place of worship was held in the Ar-Ra’uf Sangatta South Mosque, East Kutai. The target is primary school-age children in the village of South Sangatta. It is the prophecy of the prophet Muhammad SAW that the prophets of the people of the world, the Prophets of Allah SWT and the Prophet (SWT), should read the Qur'an, the Quran, the Koran, and the Scriptures. Thus, devotion through the implementation of the Islamic race in order to commemorate the Maulid of the Prophet Muhammad may include various aspects that contribute to the improvement of the spirituality, faith, and quality of life of the Muslims.